Copper Electrodeposition Kinetics Measured by Alternating Current Voltammetry and the Role of Ferrous Species. Issue 2 (1st January 2016) - Wagner, Mary-Elizabeth; Valenzuela, Rodrigo; Vargas, Tomás; Colet-Lagrille, Melanie; Allanore, Antoine
Abstract : Impurities and additives play a key role in copper electrodeposition, in particular in upstream processes such as electrowinning or electrorefining. One common impurity is iron, mostly present as iron species Fe(II) in highly concentrated sulfuric acid solutions and in a cathodic environment. Herein, the kinetics of copper electrodeposition from such solutions have been investigated using a copper rotating disk electrode and alternating current voltammetry (ACV). For a concentration of proton of 1.84 M and a concentration of Fe(II) ions of 0.054 M, the deposition kinetics are slow enough to separately observe the two electron transfer steps involved in copper reduction: an observation unique to ACV. The results suggest that Fe(II) ions affect the electrodeposition kinetic by slowing down reaction kinetics, in particular slowing the second electron transfer reaction.